Penerapan konsep kejawen pada rumah tradisional Jawa (ARTEKS : Jurnal Teknik Arsitektur, 2020)
The application of kejawen concept on Javanese traditional housesJavanese society has a unique philosophy of life. It is known as kejawen and is applied in daily life, manifested in symbols and rituals pertaining to their houses. A house for the Javanese is not merely a place to live, but it is also a place to represent many symbols reminding the philosophy that gives power to the owner. Javanese traditional houses have already been previously researched, but many of these researches emphasized more on the physical aspects, rather than on philosophy of kejawen, which try to comprehend the reality intuitively. In order to gain a deep understanding on this matter, field observation was carried out for certain period of time, using descriptive qualitative approach. The research result shows that the Javanese house shows a perfect union between macro cosmos and micro cosmos. Omah’or house is derived from the word "Om"and “Mah”. ’Om’ means the father of space and "Mah" ‘lemah’/land means the mother of the earth. ‘Omah’ for Javanese people is a manifestation of macros and micro cosmos.© 2020 Bintang Padu Prakoso, Herman Wilianto
Keywords: Javanese house; Javanese philosophy; Kejawen; Symbols